Thermal fluctuations of the optical properties of nanomechanical photonic metamaterials - Li, Jinxiang (2023)
The combination of optical and mechanical resonances offers strong hybrid nonlinearities, bistability, and the ability to efficiently control the optical response of nanomechanical photonic metamaterials with electric and magnetic field. While optical resonances can be characterized in routine transmission and reflection experiments, mapping the high-frequency mechanical resonances of complex metamaterial structures is challenging. Here, it is reported that high-frequency time-domain fluctuations in the optical transmission and reflection spectra of nanomechanical photonic metamaterials are directly linked to thermal motion of their components and can give information on the fundamental frequencies and damping of the mechanical modes. This is demonstrated by analyzing time-resolved fluctuations in the transmission and reflection of dielectric and plasmonic nanomembrane metamaterials at room temperature and low ambient gas pressure. These measurements reveal complex mechanical responses, understanding of which is essential for optimization of such functional photonic materials. At room temperature the magnitude of the observed metamaterial transmission and reflection fluctuations is of order 0.1% but may exceed 1% at optical resonances.